2013
DOI: 10.1063/1.4827094
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 30 μW terahertz source by a high-Tc superconductor mesa structure

Abstract: Using a modified mesa structure of high-T c superconducting Bi 2 Sr 2 CaCu 2 O 8þd with a thin underlaying base superconductor ($3 lm), the effective working temperature of the continuous and monochromatic terahertz emitter is extended up to 70 K, and the maximum power of $30 lW at 0.44 THz is achieved at the relatively high temperature of T b ¼ 55 K in a low bias current retrapping region. The diverging behavior of the intensity occurring at 55 K in the low current regime without hot spot formation may provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 32 publications
2
75
0
Order By: Relevance
“…Emission frequencies range from 0.3 to 2.4 THz. For the best stacks, an emission power P e in the range of tens of µW has been achieved 17,19,20,32,33 , and arrays of mesas showed emission with P e up to 0.61 mW 19 . The physics of the huge IJJ stacks is affected by Joule heating 1, 3,5,6,8,13,18,22,26,30,49,52,54,55,63 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Emission frequencies range from 0.3 to 2.4 THz. For the best stacks, an emission power P e in the range of tens of µW has been achieved 17,19,20,32,33 , and arrays of mesas showed emission with P e up to 0.61 mW 19 . The physics of the huge IJJ stacks is affected by Joule heating 1, 3,5,6,8,13,18,22,26,30,49,52,54,55,63 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been found that the linewidth of radiation is much narrower in the high-bias regime than at low bias 12,60 . Other properties such as the emission frequency seem to be basically independent of the hot spot position, leading to some debate as to whether the hot spot is helpful for radiation or just coexists with the radiating regions 20,22,23 . In fact, recent results showed that there is a strong interaction 28 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing demand of miniaturization in superconducting devices applied to the detection of different types of radiation [1][2][3][4][5] and magnetic signals [6][7][8] has triggered the study of thermodynamic and transport properties of high-T c superconducting materials at the micro and nanoscale. Since many of these devices operate in the mixed state, understanding the change in thermodynamic and structural properties of vortex matter when reducing the number of vortices down to the nanoscale is crucial for predicting their working-range.…”
Section: Introductionmentioning
confidence: 99%
“…Stacks of these natural Josephson junctions, which are referred to as intrinsic Josephson junctions (IJJs), can generate an AC Josephson current in the THz frequency range by application of a voltage, and the THz wave emission is attributed to the generation of this current. Intense THz emissions have been reported for IJJs fabricated in a mesa geometry, which itself behaves as a cavity resonator, and thus, a number of studies on such IJJ mesas have been carried out both experimentally [4][5][6][7][8][9][10][11][12][13][14][15] and theoretically [16][17][18][19][20][21][22][23][24][25][26]. However, in the previous studies, little attention was given to the state of the polarization of the THz waves.…”
mentioning
confidence: 99%